Superconductor - Moyses Luiz, Adir (IntechOpen, 2010)
This book contains a collection of works intended to study theoretical and experimental aspects of superconductivity. Here you will find interesting reports on low-Tc superconductors (materials with Tc 30 K). Certainly this book will be useful to encourage further experimental and theoretical researches in superconducting materials.